Analisis Peran dan Fungsi Pengurus Aparna Graha Utama A. Yani di Kota Surabaya - Rosyidah, Laely; Widiyarta, Agus (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2024)
Housing needs are one of the basic human requirements. The construction of simple rental apartment buildings, owned by the East Java Provincial Government and referred to as simple apartments, is expected to help meet the housing needs of the population residing in Surabaya and its surrounding areas. This should requires effective management for proper operation. PT. Jatim Grha Utama, through the Badan Pelaksana Aparna Graha Utama A. Yani, is authorized to carry out operational activities for managing the provincial government's apartment buildings. This research employs a qualitative method with primary data sources obtained from interviews with management officials and secondary data derived from articles, journals, books, and internal documents. The study's findings on the functions of the POAC management indicate that the management conducted by Bapel Aparna Graha Utama A. Yani is generally in line with expectations, although occasional challenges are encountered in the implementation phase, such as resident complaints, which are effectively addressed.